From intern to "accepted": A guide to preparing for fellowship in emergency medicine. Issue 1 (23rd June 2022) - Schnapp, Benjamin H.; Cassara, Michael; Fisher, Jonathan; Guttman, Joshua; Kayden, Stephanie; Kivlehan, Sean M.; Kuzel, Aaron R.; Reznek, Martin A; Schertzer, Kimberly; Sun, Wendy W.; Rathlev, Niels
Abstract: Introduction: The number of fellowship options for emergency medicine (EM) physicians continues to expand. While guides exist to help residents explore individual fellowship pathways, we aimed to create a comprehensive guide for all residents considering fellowship. Methods: At the direction of the Society for Academic Emergency Medicine (SAEM) Board, 9 members of the Fellowship Guide Workgroup, including members of the Fellowship Approval Committee, and 2 members of SAEM Residents and Medical Students (RAMS) group collaboratively developed the guide using available evidence and expert opinion when high‐quality evidence was unavailable. The guide was reviewed and approved by all members. Results: The guide offers advice to EM residents on how to conceptualize key aspects of their training with respect to preparation for fellowship, including scholarship, teaching, leadership, and electives. Additionally, it offers perspective on selecting a fellowship that matches the resident's interests and goals and successfully applying. Conclusion: This fellowship guide for EM residents considering fellowship summarizes the best currently available advice for residents considering fellowship training after residency.